A cidadania, o universalismo e a diferença - Paulo Manuel Costa (Ciências Sociais Unisinos)
The contemporary debate on citizenship has been dominated by three theoretical currents: liberalism, communitarianism and republicanism. It reveals different ways of conceptualising citizenship and thus a diversity of proposals for the design and organization of political institutions. In this article we intend to grasp how these theories deal with the specific issue of difference and cultural diversity. The systematization of the debate was made with reference to four thematic axes: first, the relationship to be established between the public sphere and the private sphere; as a function of this joint, which identity prevails in the political community; thirdly, what is the role assigned to political participation; and, finally, the reflexes that citizenship may have on social cohesion of the political community. The existence of a core of common values and principles is essential to the stability and cohesion of the community, but it must be able to incorporate the difference in order to develop an identity that can be shared by various cultural and ethnic groups and thus prevent exclusion, marginalization and oppression. The best way to ensure quantitative and qualitative expansion of citizenship seems to be one that promotes the participation and involvement of individuals and groups in the process of (re)definition of common values and principles that ensure life together. This process also seems to involve moving away from rigid and dogmatic readings of the liberal principles and the refusal of non-liberal claims and principles, particularly those that question the freedom of individuals against the political power and social groups.